2014
DOI: 10.1021/ef500995y
|View full text |Cite
|
Sign up to set email alerts
|

Can Lowering the Injection Brine Salinity Further Increase Oil Recovery by Surfactant Injection under Otherwise Similar Conditions?

Abstract: It is well-established that injecting water with significantly lower salinity than the formation water salinity may give increased oil recovery. Although less well studied, the observed low-salinity effect has drawn attention to possible benefits from combining low-salinity water with traditional enhanced oil recovery techniques, such as surfactant, polymer, alkali, etc., to make the overall recovery process more efficient. Surfactant injection, for example, reduces the interfacial tension (IFT) between the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The potential combination of low salinity water and surfactant flooding can obtain a maximum possible benefit over traditional techniques to make LSWI-EOR more efficient, and such a process is known as a hybrid method. LSWI, along with a surfactant, helps lower the IFT of the oil–brine system to certain minima, thus reducing the tendency of capillary trapping and mobilizing trapped capillary oil to the production well. Tichelkamp et al investigated the impact of surfactants on the IFT of a crude oil (light, heavy)–brine system at a low salinity condition. They observed that the IFT of the light crude oil–brine system achieved ultralow IFT in the presence of surfactant dioctyl sodium sulfosuccinate (AOT).…”
Section: Introductionmentioning
confidence: 99%
“…The potential combination of low salinity water and surfactant flooding can obtain a maximum possible benefit over traditional techniques to make LSWI-EOR more efficient, and such a process is known as a hybrid method. LSWI, along with a surfactant, helps lower the IFT of the oil–brine system to certain minima, thus reducing the tendency of capillary trapping and mobilizing trapped capillary oil to the production well. Tichelkamp et al investigated the impact of surfactants on the IFT of a crude oil (light, heavy)–brine system at a low salinity condition. They observed that the IFT of the light crude oil–brine system achieved ultralow IFT in the presence of surfactant dioctyl sodium sulfosuccinate (AOT).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the growing interest in low salinity water flooding, it has already drawn interest for possible synergies with other traditional EOR techniques like surfactants, alkalines, etc. The synergism between low salinity water flooding and surfactant flooding has already been studied by researchers. Although these studies were reported to obtain a benefit from low salinity surfactant synergy, according to most literature, the low salinity water flooding mechanism works in a very similar fashion to the surfactant flooding mechanism. Both of these methods are intended to increase the microscopic displacement efficiency via wettability alteration, oil–water interfacial tension reduction, and formation of a microemulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have explored the EOR potential via combining low salinity brine with chemical surfactant injection in the bid to increase oil production and their results show better recovery with combined process than applying either of the techniques alone [19][20][21]. Addition of surfactants has also been shown to be efficient in decreasing oil-brine interfacial tension and altering of rock surface wetness [22][23][24].…”
Section: Introductionmentioning
confidence: 99%